Demolishing the Islamic state myth : defeating the propaganda of ISIS - Mohamed Alami Musa (2015)
ISIS’ ideology centred on establishing the Islamic State is a powerful lure for global Muslims to seek salvation by emigrating to this Caliphate. The Muslim community has to develop a strong narrative to defeat the ISIS propaganda.